The Relationship Between Psychological Capital and Self Compassion Towards Psychological Well-Being of Factory Employees in Kudus - Prasetyowati, Hety Mery; Dhania, Dhini Rama (World Psychology, 2025)
The working environment in factories often demands strong physical and mental strength, which often affects the psychological condition of its employees. This study attempts to see how psychological capital and self-compassion play a role in improving the psychological well-being of factory employees in Kudus. A total of 81 factory employees who have worked for at least one year became participants in this study, selected using a purposive sampling technique. Data collection was carried out through a psychological scale that measures three main variables, namely psychological capital, self-compassion, and psychological well-being. The results of the analysis show that there is a very significant relationship between psychological capital and self-compassion with psychological well-being with rx12y of 0.763 at a p level of 0.000 (p <0.01), and an effective contribution of 58.3%. This means that psychological capital and self-compassion influence psychological well-being by 58.3% while the other 41.7% is influenced by other factors not examined in other studies. These findings emphasize the importance of the role of mental strength and a positive attitude towards oneself in facing the challenges of the world of work.